Development of an online food frequency questionnaire and estimation of misreporting of energy intake during the COVID-19 pandemic among young adults in Peru - Vega-Salas, María Jesús; Curi-Quinto, Katherine; Hidalgo-Aréstegui, Alessandra; Meza-Carbajal, Krysty; Lago-Berrocal, Nataly; Arias, Lena; Favara, Marta; Penny, Mary; Sánchez, Alan; Vimaleswaran, Karani Santhanakrishnan (Frontiers in Nutrition, 2022)
Background: The Young Lives longitudinal study switched to remote data collection methods including the adaptation of dietary intake assessment to online modes due to the physical contact restrictions imposed by the COVID-19 pandemic. The aim of this study was to describe the adaptation process and validation of an online quantitative food frequency questionnaire (FFQ) for Peruvian young adults. Methods: A previously validated face-to-face FFQ for the adult Peruvian population was adapted to be administered through an online self-administered questionnaire using a multi-stage process. Questionnaire development was informed by experts’ opinion and pilot surveys. FFQ validity was assessed by estimating misreporting of energy intake (EI) using McCrory method, and the FFQ reliability with Cronbach alpha. Logistic regressions were used to examine associations of misreporting with sociodemographic, body mass index, and physical activity covariates. Results: The FFQ was completed by 426 Peruvian young adults from urban and rural areas, among whom 31% was classified as misreporters, with most of them (16.2%) overreporting daily EI. Men had lower risk of under-reporting and higher risk of over-reporting (OR=0.28 and 1.89). Participants without a higher education degree had lower risk of under-reporting and higher risk of over-reporting (OR=2.18 and 0.36, respectively). No major difference in misreporting was found across age groups, areas, studying as main activity, being physically active or sedentary, or body mass index (BMI). Results showed a good internal reliability for the overall FFQ (Cronbach alpha=0.82). Conclusion: Misreporting of EI was mostly explained by education level and sex across participants. Other sociodemographic characteristics, physical activity, sedentary behavior and BMI did not explain the differences in EI misreporting. The adapted online-FFQ proved to be reliable and valid for assessing dietary intakes among Peruvian young adults during the COVID pandemic. Further studies should aim at using and validating innovative dietary intake data collection methods, such as those described, for informing public health policies targeting malnutrition in different contexts after the COVID-19 pandemic.